ISOTHERMAL OXIDATION BEHAVIOUR STUDY OF AL0.5COCRCUFENI HIGH ENTROPY ALLOY AT 800, 900, AND 1000ÂºC - Maulana Ma'ruf, Zaid
To encourage Indonesia to become a strong industrial country, it is necessary to increase the added value of natural resources such as metal minerals. One of the ways to increase the added value of metal minerals is by utilizing them as hightemperature materials. Nickel-based superalloys that are often used for this purpose have limitations that encourage the development of high entropy alloys (HEA) to be applied at high temperatures. In this study, Al0.5CoCrCuFeNi HEA was subjected to isothermal oxidation tests to see its potential as a hightemperature material. Al0.5CoCrCuFeNi isothermal oxidation tests were carried out at temperatures of 800, 900, and 1000ºC for 2, 16, and 40 hours to see the oxidation behavior of this alloy and observe the evolution of the microstructure. The alloy in button form was fabricated by melting the raw materials in a single arc furnace. The button was then homogenized for 10 hours at 1100 ºC using a horizontal tube furnace to reduce alloy segregation followed by cutting the button into coupons that ready for isothermal oxidation tests. Characterization of the oxidation test samples was carried out using optical microscopy, XRD, SEM-EDS, and micro vicker hardnes. In general, the as-homogenized and as-oxidized HEA Al0.5CoCrCuFeNi has a microstructure of dendrite (FCC) and interdendrite (Cu-rich FCC) areas. The hardness of the alloy is thought to be affected by the formation of precipitates in the dendrite area. Oxides formed after isothermal oxidation test include Al2O3 as the dominant protective oxide, and there are other oxides such as Cr2O3, Fe oxide (Fe3O4/Fe2O3), spinel (Co, Ni, Cu)(Al, Cr, Fe)2O4), and ((Co, Ni, Cu)O) with oxidation mechanism similar to the oxidation mechanism of group III Ni-Cr-Al alloy by Giggins and Pettit. The formation of CuO at high temperatures is thought to originate from the oxidation of Cu-rich interdendrite areas. The oxidation behavior of HEA Al0.5CoCrCuFeNi follows parabolic oxidation kinetics with oxidation rate constant (K) values for 800, 900, and 1000°C being 0.0320; 0.0487; and 0.1535 mg.cm-2.h-1, respectively. The activation energy value of oxide formation (Q) of this alloy is 87,646 kJ/mol.